Talent Management In The Perspective Of Human Resource Management: A Systematic Literature Review - Rina Indra Sabella; Fahmi Ashari S Sihaloho (International Journal of Economics, Science, and Education, 2025)
Purpose:Talent management has become a strategic issue in Human Resource Management (HRM) as organizations face increasing competition, talent shortages, and dynamic business environments. This study aims to systematically review and synthesize the existing literature on talent management from an HRM perspective, providing an integrated understanding of its key concepts, practices, influencing factors, and organizational outcomes. Design/methodology/approach:This study employs a systematic literature review by analyzing peer-reviewed journal articles published between 2014 and 2024 and indexed in reputable academic databases such as Scopus and Google Scholar. The review process follows PRISMA guidelines with clearly defined inclusion and exclusion criteria to ensure transparency and methodological rigor. Findings:The findings indicate that talent management within the HRM framework primarily involves talent identification and acquisition, talent development, performance management, retention strategies, and succession planning. The literature also reveals that leadership support, organizational culture, strategic alignment, and employee engagement are key factors influencing the effectiveness of talent management practices. Moreover, effective talent management is consistently associated with improved employee performance, organizational commitment, and overall organizational performance. Research limitations/implications: This review is limited to selected databases, publication periods, and English-language journal articles, which may constrain the comprehensiveness and generalizability of the findings. Future research is encouraged to conduct empirical studies and explore talent management practices across different organizational and cultural contexts. Pracical implications: The results provide practical insights for HR managers and organizational leaders in designing and implementing integrated talent management strategies aligned with organizational goals to enhance sustainable performance. Originality/value:This study offers an integrative synthesis of talent management literature within the HRM perspective and identifies research gaps that can guide future studies in the field. Paper type:Literature review Keyword: talent management; human resource management; systematic literature review; employee performance; organizational performance.